Предмет: Алгебра,
автор: lchashhina1
1.Преобразуйте в многочлен a)(c+2)(c-3)-(c+1)(c+3) б)(4x-3)²-6x(4-x) в)(b+3)(b-3)+(2b+3)²
2.Найдите значение выражения (3a+b)²-(3a-b)² при a= 3⅓,b=-0,3
3.Упростите выражение
8(5y+3)²+9(3y-1)²
Ответы
Автор ответа:
0
1.
а) (c+2)(c-3)-(c+1)(c+3)= -5с-9
б) (4x-3)²-6x(4-x)= -2x²-24x+9
в) (b+3)(b-3)+(2b+3)²= 5b²+12b= 5(b+12/5)b
2.(3a+b)²-(3a-b)²=12ab=12 × 1 ×(−0,3) = −3,6
3.8(5y+3)²+9(3y-1)²=281y²+186y+81
а) (c+2)(c-3)-(c+1)(c+3)= -5с-9
б) (4x-3)²-6x(4-x)= -2x²-24x+9
в) (b+3)(b-3)+(2b+3)²= 5b²+12b= 5(b+12/5)b
2.(3a+b)²-(3a-b)²=12ab=12 × 1 ×(−0,3) = −3,6
3.8(5y+3)²+9(3y-1)²=281y²+186y+81
Похожие вопросы
Предмет: Математика,
автор: Saigac
Предмет: Химия,
автор: ledovskayaangelina61
Предмет: Экономика,
автор: shaydullin228
Предмет: Литература,
автор: yevgeniylagun